Improving Writing Skills Through Good Paraphrasing Techniques in Fourth Semester Tadris Bahasa Inggris Students - Delfia Herwanis Wahid; Astri Juraini; Rahmanita Zakaria (ISTIFHAM, 2023)
This study is an example of classroom action research. This study aims to help Tadris Bahasa Inggris (TBI) students in their fourth semester develop their writing abilities through appropriate and effective paraphrasing methods. The participants in this study were IAIN Takengon fourth-semester TBI students. Twelve students took part in this investigation. Writing assignments in class revolve around journal paraphrases. The Middle Test scores of Tadris Bahasa Inggris students in the fourth semester and student observation notes on the learning process using the paraphrase technique were used to compile the data for this study. The outcomes demonstrated that students may achieve satisfactory grades. Consequently, using a decent paraphrasing technique can help students become more adept.